Application of Encapsulation Technology in Edible Films: Carrier of Bioactive Compounds - Chaudhary, Vandana; Thakur, Neha; Kajla, Priyanka; Thakur, Shubham; Punia, Sneh (Frontiers in Sustainable Food Systems, 2021)
Nutraceuticals, functional foods, immunity boosters, microcapsules, nanoemulsions, edible packaging and safe food are the new progressive terms, adopted to describe the food industry. Also the rising awareness among the consumers regarding these has created an opportunity for the food manufacturers and scientists worldwide to use food as a delivery vehicle. Packaging performs a very imminent role in the food supply chain as well as it is a consequential part of the process of food manufacturing. Edible packaging is a swiftly emerging art of science in which edible biopolymers like lipids, polysaccharides, proteins, resins etc. and other consumable constituents extracted from various non-conventional sources like microorganisms are used alone or imbibed together. These edible packaging are indispensable and are meant to be consumed with the food. This shift in paradigm from merely using food packaging as a source of protection to edible, environment friendly, delivery vehicles for bioactive compounds have opened new avenues for the packaging industry. This shift in paradigm from traditional food packaging to edible, environment friendly, delivery vehicles for bioactive compounds have opened new avenues for the packaging industry. Bioactive compounds imbibed in food systems are gradually degenerated, or may change their properties due to internal or external factors like oxidation reactions, or they may react with each other thus reducing their bioavailability and ultimately may result in unacceptable color or flavor. A combination of novel edible food packaging material and innovative technologies can serve as an excellent medium to control the bioavailability of these compounds in food matrices. One promising technology for overcoming the aforesaid problems is encapsulation. It can be used as a method for entrapment of desirable flavors, probiotics or other additives in order to apprehend the impediments of the conventional edible packaging. This review explains the concept of encapsulation by exploring various encapsulating materials and their potential role in augmenting the performance of edible coatings/films. The techniques, characteristics, applications, scope and thrust areas for research in encapsulation are discussed in detail with focus on development of sustainable edible packaging. Keywords: edible packaging; encapsulation; nanoemulsions; bioactive compounds